The Original Fish Fight: The Newlyn Fish Riots of 1896 - Sutton, Josh (Petits Propos Culinaires, 2014)
An account of an outbreak of lawlessness between local Newlyn fishermen and interlopers from the East Coast in 1896 and the role played by the coming of the railways to the furthest reaches of the Cornish peninsula.